The Impact of Innovation, Knowledge Spillovers and Oil Prices on Economic Growth of the Regions of Kazakhstan - Mukhamediyev, Bulat; Spankulova, Lazat (International Journal of Energy Economics and Policy, 2020)
The study of impact of innovation and diffusion of knowledge for economic growth of European regions and other developed countries is increasingly attracting attention of scientists. Along with this, there are many studies for impact of world economic growth of oil prices. At the same time, there is an insufficient attention to joint assessment and comparative analysis of effectiveness of these internal and external growth factors. Moreover, this important issue has been studing a little in relation to countries with economies in transition. This paper is devoted to the study of the impact of innovation and the knowledge spillover in combination with an assessment of the impact of fluctuations in the world oil price on economic growth of regions of Kazakhstan. Catching-up development models are constructed according to annual data from 2005 to 2016 for 16 regions of Kazakhstan. Calculations based on the panel data with fixed effects have confirmed that costs of technological innovations, their spillovers between regions, healthcare costs, as well as the growth rate of the world oil price positively influenced for economic growth in regions. Moreover, socio-economic conditions reinforced their positive impact on growth. It has established that changes in the world oil price and costs of technological innovations and their spillovers between regions effects at the same order, and impact of health care costs and socio-economic conditions on regional growth is noticeably weaker. The results of the study confirm that for innovation activity is essential for the economic growth of the oil exporting country as well. Keywords: oil prices, R&D, innovations, knowledge spillovers, regional growth, Kazakhstan JEL Classifications: C33, O11, O32, O40 DOI: https://doi.org/10.32479/ijeep.9034